Effects of fluticasone propionate inhalation on levels of arachidonic acid metabolites in patients with chronic obstructive pulmonary disease. - Verhoeven, G T (2001)
BACKGROUND: In smoking COPD patients the bronchoalveolar lavage (BAL) fluid contains high numbers of inflammatory cells. These cells might produce arachidonic acid (AA) metabolites, which contribute to inflammation and an increased bronchomotor tone. AIMS: To investigate levels of AA metabolites in BAL fluid, before and after inhaled glucocorticoid therapy: fluticasone propionate (FP) 1 mg per day, or placebo. METHODS: A double-blind placebo controlled trial lasting six months. COPD patients were selected by clinical criteria and the presence of bronchial hyper-responsiveness (BHR). Lung function was recorded and in BAL fluid we counted cell numbers and measured LTB4, LTC4/D4/E4, PGE2, 6kPGF1alpha, PGF2alpha and TxB2. A control group consisted of asymptomatic smokers (n=6). RESULTS: Paired data were obtained from 9 FP treated and 11 placebo patients. BAL cells were almost exclusively alveolar macrophages. In patients and controls both cellularity and levels of AA metabolites were equal Cell numbers did not change after treatment. Statistically significant decreases after FP therapy were noticed for PGE2 (30%), 6kPGF1alpha (41%) and PGF2alpha (54%). CONCLUSIONS: In COPD, the capability of inflammatory cells to produce certain AA metabolites was decreased after inhaled FP treatment. This result is discussed in its relation to clinical effects, the influence of smoking, and the results of an earlier, similar study in asthma patients.